Inferior vena cava dimensions in patients with acute kidney injury - Andres Yepes-Hurtado; Sabry Omar; Khalid Monzer; Raed Alalawi; Kenneth Nugent (Southwest Respiratory and Critical Care Chronicles, 2016)
Background: Volume contraction frequently contributes to the development of acute kidney injury.  The rapid assessment of volume status in patients with acute kidney injury could improve decision making and outcomes.